Assessment of in vitro cytotoxicity and in vivo antitumor activity of Sphaeranthus amaranthoides burm.f - Gayatri, S. (Pharmacognosy Res, 2015)
BACKGROUND: A number of plants have been used in Indian system of medicine such as ayurveda, unani and siddha, but most of these plants were not explored properly. Sphaeranthus amaranthoides (SA) Burm.f., is one such plant used as an energizer in siddha. OBJECTIVE: To evaluate the anticancer effect of chloroform extract of the whole plant of SA Burm.f. against Ehrlich ascites carcinoma bearing Swiss albino mice. MATERIALS AND METHODS: The anticancer effect of chloroform extract was investigated in Swiss albino mice bearing Ehrlich ascites carcinoma at two different dose levels. Acute toxicity studies were also performed to determine the safety of the extract. Mice injected with Ehrlich ascites carcinoma cells were treated with the extract of doses 200 and 400 mg/kg body weight and standard 5-fluorouracil 20 mg/kg body weight for 15 consecutive days. Animals were sacrificed on day 15 for determination of anticancer activity by evaluating tumor volume, nonviable and viable tumor cell count and hematological parameters. RESULTS: Mice treated with the extract showed a significant decrease in tumor volume and viable cell count and an increase in nonviable cell count and mean survival time. The hematological parameters were also found to be restored to a normal level. CONCLUSION: The results indicate that the chloroform extract was producing anticancer activity comparable with that of the standard 5-fluorouracil.